Positive and Negative Impacts of Tourism on Culture: A Critical Review of Examples from the Contemporary Literature - Shahzalal, Md (2016)
Now-a-days it is a common debate that whether the negative impacts of tourism on culture outweighs its positive benefits. Some people say, it is really hard to measure that how much culture is being damaged by the tourism or how much culture is being protected due to the involvement of many socio-cultural and socio-economic variables together in tourism. From the extensive literature survey it is found that the tourists, tourism enterprises and hosts are jointly responsible not solely for damaging or keeping a culture (Spanou, 2007). This research suggests that for managing culture responsibly, a democratic management group in a destination management needed to be developed, the local community should be empowered, priority should be given to the process of the development not the product, and finally a structural link between the formal and informal sectors in the tourism industry should be lead by the government to develop a code of conducts and cultural research centres for cultural education, training, workshops, exhibitions, and performance. Keywords: Culture, Tourism, Tourists, Community, Responsible tourism plan, Tourism enterprises, Cultural touris